Resistance to Aging of Asphalt Modified with Multidimensional Nanomaterials: A literary Review - Muñoz Pérez, Socrates Pedro; Salazar Horna, Leny Arasely; Luna Pastor, Daladier (Periodica Polytechnica Civil Engineering, 2022)
Multidimensional nanomaterials, is a resource that has been formed over time becoming a revolutionary technology with a transcendent character providing the use in asphalt construction procedures, benefiting in the aspects of resistance in the environments to the field of civil engineering, in the same way it is a way in the advance for a better conservation of horizontal works with a favorable impact on the materials used, helping to preserve the care of the environment. In such a way that, in this article, a systematic review is reflected, around the exhaustive research in the databases such as Scopus and Science Direct, compiling a sum of 85 articles, which are indexed in journals from 2017 to 2021, carried out correspondingly on the different investigations of the management of multidimensional nanomaterials in asphalts. The objective of this literary review is to transmit various research by authors such as: the impact on the life cycle of asphalt, the performance it produces, the profitability and the advantage of the teaching that multidimensional nanomaterials have left, to later show results that show a growth in yields in asphalts through the application of multidimensional nanomaterials, So that it presents greater efficiency in the resistance to aging of the asphalt it is concluded that the nanomaterials reduce the environmental impact caused by the field of the constructions, improving the anti-aging capacity of the asphalt.